2019
DOI: 10.1021/acscatal.9b02613
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating Cysteine-Assisted Synthesis of Indirubin by a Flavin-Containing Monooxygenase

Abstract: Indirubin is a biologically active compound found in Danggui Longhui Wan, which is a traditional Chinese medicine for chronic myelocytic leukemia. In the biosynthesis of indirubin, the formation of indigo, which is a stereoisomer of indirubin, is a major side reaction. Recent findings have suggested that cysteine supplementation shifts product selectivity from indigo to indirubin. Here, we disclose how cysteine is involved in enhancing the product selectivity in the synthesis of indirubin using a flavin-contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…As an alternative to inhibit IG formation, cysteine (Cys) was used. Cys can provide reducing power as well as thiol moiety to retain 3‐OH‐indole and produce 2‐cysteinylindoleninone (2‐Cys‐indoleninone), which subsequently reacts with 6‐Br‐2‐oxindole to generate 6BrIR (J. Kim et al, 2019) (Supporting Information: Figure S12). Interestingly, when Cys was used in the reactions, 6BrIR was produced without IG irrespective of the ratio of 6‐Br‐2‐oxindole to 3‐OH‐indole (Figure 5a).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As an alternative to inhibit IG formation, cysteine (Cys) was used. Cys can provide reducing power as well as thiol moiety to retain 3‐OH‐indole and produce 2‐cysteinylindoleninone (2‐Cys‐indoleninone), which subsequently reacts with 6‐Br‐2‐oxindole to generate 6BrIR (J. Kim et al, 2019) (Supporting Information: Figure S12). Interestingly, when Cys was used in the reactions, 6BrIR was produced without IG irrespective of the ratio of 6‐Br‐2‐oxindole to 3‐OH‐indole (Figure 5a).…”
Section: Resultsmentioning
confidence: 99%
“…The in situ generated 3‐OH‐indole and 2‐Cys‐indoleninone react with 6‐Br‐2‐oxindole to produce 6BrIR. However, the remaining 3‐OH‐indole is oxygenated again by MaFMO to become isatin, and the produced isatin reacts with 3‐OH indole leading to IR byproduct (J. Kim et al, 2019). Therefore, the whole‐cell reaction conditions of ΔtnaA TnaA+MaFMO to generate 6BrIR without forming IR were further examined.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…23 Recently, it was shown that cysteine can shi the selectivity of a avin-containing monooxygenase from indigo to indirubin. 24 Herein, an anomaly to the innate selectivity towards indigo under indoxyl-generating conditions is explored for 7-azaindole, 5, which exclusively produces 7,7 0 -diazaindirubin, 6. In this instance, the intermediate is specically 7-azaindoxyl, 7 (Fig.…”
Section: Introductionmentioning
confidence: 99%